2016
DOI: 10.1002/btpr.2358
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular genetic improvements of cyanobacteria to enhance the industrial potential of the microbe: A review

Abstract: The rapid increase in worldwide population coupled with the increasing demand for fossil fuels has led to an increased urgency to develop sustainable sources of energy and chemicals from renewable resources. Using microorganisms to produce high-value chemicals and next-generation biofuels is one sustainable option and is the focus of much current research. Cyanobacteria are ideal platform organisms for chemical and biofuel production because they can be genetically engineered to produce a broad range of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 212 publications
(451 reference statements)
0
19
0
Order By: Relevance
“…(Johnson et al . ). Currently, very few studies reported application of a CRISPR/Cas9 genome editing system in the fast‐growing cyanobacterium S. elongatus UTEX 2973, as a proof of concept for the ability to produce a marker‐free deletion mutant to target the nblA gene (Wendt et al .…”
Section: Genome Editing Toolsmentioning
confidence: 97%
“…(Johnson et al . ). Currently, very few studies reported application of a CRISPR/Cas9 genome editing system in the fast‐growing cyanobacterium S. elongatus UTEX 2973, as a proof of concept for the ability to produce a marker‐free deletion mutant to target the nblA gene (Wendt et al .…”
Section: Genome Editing Toolsmentioning
confidence: 97%
“…However, these systems are not feasible for the production of fourth generation biofuels as many of these chemicals are volatile, thus cannot be maintained in an open system. Fourth generation biofuels are derived from genetically modified POs that directly convert CO 2 into biofuel chemicals . Another disadvantage of pond systems is the use of genetically modified POs in these systems is typically not allowed by policymakers due to the risk of these strains contaminating the surrounding environment.…”
Section: Large‐scale Cultivation Systems For Microalgae and Cyanobactmentioning
confidence: 99%
“…Diversity of hydrocarbons produced by Cyanobacteria in terms of chain length, degree of saturation, and variations of the carbon skeleton has been highlighted by Xie et al (2017). Considerable efforts have been directed to metabolic engineering of Cyanobacteria, mainly geared towards biofuel production (Al-Haj et al 2016; Oliver et al 2016; Johnson et al 2016; Gomaa et al 2016). The major optimization strategies were directed towards improving carbon fixation (Atsumi et al 2009), improving the capture of the light energy (Iwaki et al 2006), and improving product extraction by the use of induced autolysis systems (Miyake et al 2014).…”
Section: Cyanobacteria: the Potential To Derive Biomass From Solar Enmentioning
confidence: 99%